RANA LAKE REVITALIZATION STUDIES USING LOCAL WISDOM APPROACH IN BURU ISLAND, MALUKU PROVINCE - Enik Kristiana; Andrianto Kusumoarto; Rahmat Rejoni (Universitas Indraprasta PGRI, 2023)
Rana Lake is a lake on Buru Island, Maluku Province, which is a tourist attraction with various benefits in it and cultural tourism of the Rana Tribe, who make the lake sacred to uphold the potential of local wisdom. By utilizing the water in Lake Rana with the principles of good water resources management, we can reap various benefits for the needs and needs of the community, such as: Irrigation & agriculture, drinking water for humans & animals, tourism for preservation & improvement of the community's economy. Lake Rana has a positive potential (+) in the form of quite large water resources, namely the condition of the area and water quality is quite good and a negative potential (-) in the form of problems faced, namely Lake Rana is in an area of customary land which is difficult to access and needs to be engineered technique. With these problems, it is necessary to arrange the area as a natural tourist spot based on local wisdom. This study aims to identify problems with the existing economic, socio-cultural conditions of the area and analyze the return of important functions and benefits from the lake through Lake Rana Revitalization. The method used in this study is descriptive quantitative and qualitative research with an empirical approach to cultural substance, namely the local wisdom approach, namely identifying existing conditions and identifying problems as well as the spatial analysis stage, with an approach that takes into account facts and realities in the field, so that there is continuity tendencies towards better completion and drafting by maintaining traditions and local wisdom as well as the sustainability of cultural values and welfare heritage.